THE PLACE OF PROFESSIONAL EDUCATION SYSTEM IN FORMATION OF GRADUATES' COMPETITIVENESS - G. F. Shafranov-Kutsev; G. Z. Efimova (Russian State Vocational Pedagogical University, 2019)
Introduction. Insufficient competitiveness of Russia is one of the key problems constraining scientific, technological, social and economic development of the country. Scientific interest is the formation of youth competitiveness as the special social and demographic group having a strategic importance for the country. In the course of population competitiveness formation, the leading place is taken by an education system and professional education.The aim of the present publication was to scientifically judge modern professional education system aspects directed to formation of a competitive orientation and competitiveness of the younger generation. The sociological research described in the article is devoted to studying of practical application of the competencies received in institutions of professional education by working youth before their admission to employment.Methodology and research methods. The review and synthesis of scientific sources content corresponding to the announced subject and research problems were performed at theoretical stage of the research. In the course of empirical stage, social questionnaire survey was conducted among the working youth (N=956). Acquired data were processed using the license version of the SPSS programme. In addition, the selective secondary (comparative) analysis of social science research, conducted by Russian and foreign scientists, was applied.Results and scientific novelty. The issues of formation of competitive orientation and competitiveness, competitive competencies of the personality are considered according to social standpoints. It is noted that the higher the education level of the respondent is, the more positive the self-assessment of his or her competitiveness is. The working young people with the higher education show the highest level of self-assessment of competitiveness. Certain characteristics of modern youth, influencing on modernisation of institutions of professional education, are disclosed. Today, the main task of students is the acquisition of skills of orientation and navigation in the information flow and space of powerful socio-cultural transformations. Therefore, the education system is forced to be reconstructed for preparation of holders of complex knowledge and competencies, generators of newideas and projects. Consequently, there is the demand for the development of individual educational  programmes and modules, freedom of access for students to new resources and technologies, change of functions and competencies of pedagogical workers.The conclusion is drawn that the assessment of own competitiveness acts as the defining factor of the relation to the chosen field of occupation. The respondents focused in the labour sphere on competitive strategy more often recognise insufficiency of knowledge and competencies received by them during the learning process in educational institution. The direct consequence and the indicator of high level of competitiveness is high income level of young specialists. The working young people, who consider themselves competitive, note more often: satisfaction with their occupation; compliance of the work responsibilities with the profession obtained; availability of several professions. The representatives of this category of respondents consider their professional choice as the right and final, characterising themselves as executive, efficient and prospective employees.Practical significance. The undertaken research enriches sociological theory with new knowledge on competitiveness of young people. The materials of the research can be applied in the system of education to design the recommendations on formation and development of necessary qualities in the studying youth. Moreover, the outcomes of the present research can be useful for the heads and administrators of organisations and enterprises, who are engaged in successful professional adaptation of young employees.